Dimensi Teologis-Praktis Prinsip al-Asma’ dalam Surah Hud Ayat 123: Upaya Kontekstualisasi Moderasi Beragama di Indonesia - Akib, Moh; Najih, Moh Ghundar (Al-Qudwah, 2025)
This article aims to investigate the principle of al-Asma’ in the Qur’an, with particular focus on Surah Hud, verse 123, and to contextualize it within the framework of religious moderation in Indonesia. The principle of al-Asma’ underscores that the names of Allah encompass complementary meanings that can guide the attainment of equilibrium between theological understanding and practical life. This study aims to situate the principle as a response to contemporary challenges confronting religious moderation, including social polarization, radicalism, and interreligious conflict. Methodologically, the research employs a thematic exegesis (tafsir maudhu‘i) approach combined with semiotic analysis, integrating textual interpretation of the Qur’an with the socio-religious realities of Indonesia. Primary data are drawn from the analysis of pertinent Qur’anic verses, classical and contemporary exegetical literature, as well as empirical studies concerning the practice of religious moderation within society. The findings indicate that a comprehensive understanding of the names of Allah in Surah Hud [11]:123 can provide a conceptual framework for advancing religious moderation. The singular meaning of Allah’s name affirms His oneness and sovereignty, while paired attributes such as Al-‘Aziz and Al-Hakim exemplify a balance between justice and wisdom. This interpretation supports the cultivation of a social ethic rooted in tolerance, empathy, and peaceful coexistence among religious communities. This study contributes to bridging theological exegesis and social praxis by positioning the principle of al-Asma’ as a foundational framework for preachers, educators, and policymakers to develop an inclusive and contextually relevant Islamic narrative that addresses the dynamics of religious life in Indonesia.Abstrak: Artikel ini bertujuan mengkaji kaidah al-Asma’ dalam Al-Qur’an, khususnya sebagaimana termaktub dalam Surah Hud ayat 123, dengan mengaitkannya pada konteks moderasi beragama di Indonesia. Prinsip al-Asma’ menegaskan bahwa nama-nama Allah memiliki makna yang saling melengkapi dan dapat dijadikan pedoman dalam membangun keseimbangan antara teologi dan praksis kehidupan. Penelitian ini berupaya mengontekstualisasikan prinsip tersebut sebagai respon terhadap tantangan moderasi beragama, seperti polarisasi sosial, radikalisme, dan konflik antarumat beragama. Metode yang digunakan adalah pendekatan tafsir tematik dengan analisis semiotik, yang memadukan telaah teks Al-Qur’an dengan realitas sosial keagamaan di Indonesia. Data utama diperoleh dari analisis ayat-ayat relevan, literatur tafsir klasik dan kontemporer, serta studi empiris terkait praktik moderasi beragama di masyarakat. Hasil penelitian menunjukkan bahwa pemahaman komprehensif terhadap nama-nama Allah dalam Surah Hud ayat 123 dapat menjadi basis konseptual bagi moderasi beragama. Makna tunggal dari nama Allah menegaskan aspek keesaan dan kekuasaan-Nya, sedangkan makna gandengan seperti Al-‘Aziz dan Al-Hakim mencerminkan keseimbangan antara keadilan dan kebijaksanaan. Pemaknaan ini mendorong pembentukan etika sosial yang menekankan toleransi, empati, dan koeksistensi damai antarumat beragama. Kontribusi penelitian ini terletak pada upayanya menjembatani tafsir teologis dan praksis sosial, menjadikan prinsip al-Asma’ sebagai landasan bagi para dai, pendidik, dan pembuat kebijakan dalam mengembangkan narasi keislaman yang inklusif dan kontekstual terhadap dinamika keberagamaan di Indonesia.